Analysis of Interest for Development of Digital Business Department at Diploma II Level at The Proficisional Instituto Sāo Joāo Batista Timor Leste In 2024 - Antonio Guterres; Manuel Pinto; Andre Pereira Gaspar; Luis Fernandes; Basilio dos Santos da Silva; Aquelino da Costa Tilman; Pedro Menezes Amaral (Green Publisher Indonesia, 2025)
This study aims to assess the interest of Timorese people in the development of digital business knowledge at the higher education level, especially in facing the digitalization era of industry 4.0 which has affected global marketing. The development of digital technology, such as the digital economy, internet economy, and knowledge-based innovation, is an important foundation in this study. The research method used is descriptive qualitative, with data collection techniques including in-depth interviews, online and offline questionnaires, field observations, document analysis, and focus group discussions (FGDs). Data was collected to prove the community's interest in the plan to open a Digital Business major at Instituto Profissional Sao Joao Batista (IPJB) Dili. The results showed that of the 387 respondents interviewed and observed in 14 districts, including the Oecusse region, the majority (57.4% or 222 respondents) approved of the opening of the major, while only 0.5% (2 respondents) disagreed. Respondents also showed a good understanding of the internet and digital marketing, with dominant use of the internet for activities such as online shopping, online sales, and academic and personnel needs. Based on these findings, it is concluded that the implementation of digital business is essential to improve the quality of human resources and support the growth of a modern economy in the industrial era 4.0, especially for the younger generation in the future.